Partnership and digital transformation for citizen-centric services aligned with the government in your hand initiative (African Journal of Public Administration & Management, 2026)
Citizens globally expect faster, transparent, and convenient services. The Ministry of Housing and Urban Development is digitizing two ncritical processes:Land Disposal (Sale of Land)Building Permit Application and ApprovalCurrent systems are fully manual, slow, and inefficient, limiting the GIYH vision